2020
DOI: 10.3897/herpetozoa.33.e51338
|View full text |Cite
|
Sign up to set email alerts
|

Dead snakes and their stories: morphological anomalies, asymmetries and scars of road killed Dolichophis caspius (Serpentes, Colubridae) from Romania

Abstract: We analysed several morphological characters of 84 road-killed D. caspius individuals from different areas of southern Romania. Most presented asymmetries in the total number of temporal scales, the temporal row and the periocular and labial scales. Almost a quarter of snakes had scars, located especially on the head and tail; many individuals had multiple injuries. The lowest rate of individuals with scars was found in the area with the least anthropogenic impact (Danube Gorge). This finding suggests that, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Recent studies have indicated that road-killed animals could provide ecological or zoogeographic information (e.g. Teodor et al, 2019;Ile et al, 2020). Road-killed C. hungaricus records in Northwestern Romania confirm this fact.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Recent studies have indicated that road-killed animals could provide ecological or zoogeographic information (e.g. Teodor et al, 2019;Ile et al, 2020). Road-killed C. hungaricus records in Northwestern Romania confirm this fact.…”
Section: Discussionmentioning
confidence: 86%
“…At the same time, investigating other roads from the region, or the same road but on a longer period would make possible investigations on the species activity cycle, which has two peaks (Bérces & Elek, 2013). Thus, studying road-killed animals proves its value one more time, succeeding to offer information without any impact on living specimens, a fact recently indicated in Romania in the case of other animals (Ile et al, 2020). Regarding the impact of roads on biodiversity in the Carei Plain, we consider that the most important conservation decision should be to stop further road modernisation in the region.…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, we made several excursions to the Yampil vicinities between 26 and 28 September 2021: large abandoned quarry in the eastern part of the town, adjacent territories, old and new cemeteries, jewish cemetery between Yampil and Porohy, steppe slopes, pits, roads and small streets in industrial districts were searched. Special attention was paid to roads, because it is well known that the Caspian whipsnakes are common victims of traffic (Covaciu-Marcov et al, 2012;Ile et al, 2020). During these surveys we had registered the green lizard, Lacerta viridis (Laurenti, 1768), the grass snake, N. natrix, and the dice snake, N. tessellata.…”
Section: Resultsmentioning
confidence: 99%
“…The road through IGNP may be a useful focus for other studies which examine the carcasses of road-killed animals. Such uses of road-killed vertebrates' carcasses have been mentioned recently in studies concerning feeding ecology, parasites, morphology and age structure (e. g. McAllister et al 2016;Kolenda et al 2019a,b;Vafae Eslahi et al 2017;Ile et al 2020;Maier et al 2020). The road could also be used as a source of samples in the case of invertebrates, including rare species, such as E. carpathicus.…”
Section: Discussionmentioning
confidence: 99%